Isolation of four types of bacteria that cause kidney damage in broiler chickens: Harith M. Al-Hiyali , Haidar T. Al-Kabbi and Suad Abdulkarim - Al-Hiyali, Harith M. (The Iraqi Journal of Veterinary Medicine, 2005)
This study was conducted on 80 cases of damaged kidneys received bypoultry disease diagnostic centers in Baghdad. Four microorganisms were isolatedE.coli , Proteus milabilis , Pseudomonas aregenosa and Klebsiella pneumoniaand formed 55, 22.5 , 17.5 ,and 5% of the infection respectively . While no anykind of bacteria were isolated from kidneys of healthy chicks. To be sure the E.coli could be a cause of kidney damage. An experimental infection with E.coliwas carried out on 40 chicks, three weeks old, and randomly divided into twogroups. Chicks of the first group was inoculated intravenously with 0.5 ml of fieldisolated E. coli suspension containing 2x107 colony forming unit (CFU), while thesecond group was inoculated with 0.5 ml distilled water and considered as controlgroup. The results revealed that chicks inoculated with E.coli showed 70%mortality rate with severely congested swollen kidneys with acute interstitialnephritis. However, this study gave information on kidney damage widely spreadat this time; therefore, it could be recommended for other studies to be hold in thefuture on the other causative agents of each case.